Constraining dust extinction properties via the VVV survey - Majaess, Daniel; Dékány, István (Astronomy and astrophysics, 2016)
Near-infrared color-excess and extinction ratios are essential for establishing the cosmic distance scale and probing the Galaxy, particularly when analyzing targets attenuated by significant dust. A robust determination of those ratios followed from leveraging new infrared observations from the VVV survey, wherein numerous bulge RR Lyrae and Type II Cepheids were discovered, in addition to BVJHKs(3.4 → 22) μm data for classical Cepheids and O stars occupying the broader Galaxy. The apparent optical color-excess ratios vary significantly with Galactic longitude (ℓ), whereas the near-infrared results are comparatively constant with ℓ and Galactocentric distance (\hbox{$\langle E(J-\overline{3.5~μ {\rm m}})/E(J-K_{\rm s}) \rangle =1.28\,±\,0.03$}). The results derived imply that classical Cepheids and O stars display separate optical trends (RV,BV) with ℓ, which appear to disfavor theories advocating a strict and marked decrease in dust size with increasing Galactocentric distance. The classical Cepheid, Type II Cepheid, and RR Lyrae variables are characterized by ⟨AJ/E(J−Ks)⟩ = ⟨RJ,JKs⟩ = 1.49 ± 0.05 (⟨AKs/AJ⟩ = 0.33 ± 0.02), whereas the O stars are expectedly impacted by emission beyond 3.6 μm. The mean optical ratios characterizing classical Cepheids and O stars are approximately ⟨RV,BV⟩ ~ 3.1 and ⟨RV,BV⟩ ~ 3.3, respectively.